Study About The Usage of Twitter and The Relationship with TV Show in Indonesia - Badjened, Noura Hassan; Erwin, Alva; Eng, Kho I (Swiss German University, 2016)
The uses of social media every year has been explodes due to more new social media have invented, including their new function. Twitter has become a well-known social media, as it allow user to share short text message called tweets that can be contain of text or URL, twitter can be used as broadcasting media since every user can create about any topics they desire. And some topics contain TV program conversation, realizing this huge opportunity. Many TV station have the official Twitter account to reach their viewers by giving information and creating Hastag to group up the conversation. So the TV station can get indirectly feedback.